2016
DOI: 10.1186/s13054-016-1302-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on thromboelastometry and platelet aggregation in cardiac arrest patients undergoing targeted temperature management

Abstract: BackgroundCoagulation can be visualised using whole blood coagulation analyses such as thromboelastometry and platelet aggregation tests; however, the role of temperature in the analyses is ambiguous. The aim was to examine whether temperature influences the whole blood coagulation tests.MethodsWe included 40 patients treated with targeted temperature management (33 ± 1 °C) after out-of-hospital cardiac arrest. The blood samples were obtained on hypothermia and normothermia. Each blood sample was analysed simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…Another explanation of this phenomenon may be a cold-induced decrease in bone marrow function [40]. The persistent decrease in a platelet count, which was observed in the observed group after rewarming, may also be explained by perioperative blood loss (during pPCI), which is consistent with previous studies involving invasively-treated patients [29]. TEG analysis of fibrinolysis dynamics was brought to a conclusion that one of the possible mechanisms leading to reduced clot solubility during therapeutic hypothermia is a higher secretion of tissue plasminogen activator by endothelial cells and a slower conversion of plasminogen to plasmin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another explanation of this phenomenon may be a cold-induced decrease in bone marrow function [40]. The persistent decrease in a platelet count, which was observed in the observed group after rewarming, may also be explained by perioperative blood loss (during pPCI), which is consistent with previous studies involving invasively-treated patients [29]. TEG analysis of fibrinolysis dynamics was brought to a conclusion that one of the possible mechanisms leading to reduced clot solubility during therapeutic hypothermia is a higher secretion of tissue plasminogen activator by endothelial cells and a slower conversion of plasminogen to plasmin.…”
Section: Discussionsupporting
confidence: 89%
“…Variables resulted during both analyses were comparable [21,25,29]. The R variable, corresponding to clotting time in ROTEM ® , is the value most influenced by activity of coagulation factors.…”
Section: Discussionmentioning
confidence: 83%
“…40 Platelet function was more incisively studied in a series of 82 patients undergoing therapeutic cooling after out-of-hospital cardiac arrest, which confirmed an impairment of platelet function assessed by various techniques in hypothermic patients. 41,42 Another laboratory study in 171 patients who were treated with cooling down to either 33°C or 36°C found lower platelet counts in the most intensely cold patients and thromboelastographic changes, compatible with hypocoagulability, in some patients. 43 A more precise study on coagulation function in 21 patients who were subjected to therapeutic cooling showed delayed clot formation, impaired clot stability, and enhanced endogenous fibrinolysis.…”
Section: Hemostasis and Hypothermiamentioning
confidence: 99%
“…The study is registered in ClinicalTrails.gov (identifier: NCT02733146). Of the 42 patients included, 21 patients have previously been described by Jeppesen et al When preparing the article, the STROBE guidelines were followed.…”
Section: Methodsmentioning
confidence: 99%